Ergonomic Risk Level Assessment in Building Process, Automobile Tire Manufacturing - Supooto, Asanee; Seeprasert, Prapamon; Katramee, Anchalee (Journal of Health Science and Alternative Medicine, 2020)
Background: Ergonomic problem among employees who are working in a workplace could induce the performance of employee in either positive or negative direction. Therefore, fixing ergonomic problems in a particular place could be improvement the productivity of a company. Methods: Ergonomic risk in the building process, automobile tire manufacturing at a plant in Rayong Province, Thailand were evaluated by using a cross-sectional study. The rapid entire body assessment (REBA) was used as a tool to detect the ergonomic risk and its levels among employees. Results: Five tasks or processes of work were found at risk index level 4 which were required immediate improvement or correction; i) pulling the raw cover out of the tire-forming machine, ii) peeling the tread, iii) changing the bead ring in the machine, iv) removing the raw rubber clog in the processing machine, called an extruder, and v) lifting the tread onto the tire building machine. Filling the steel grid with metal powder was found at risk level-3 which was required for further investigation and improvement. Lastly, at the department of the rubber sheet on softer steel called shin-gane was found at risk level 2 which was required to be investigated and continuously monitored. Conclusion: The findings of risk assessment from this study could be used for establishing the tire manufacturing safety measures or development a guideline to reduce the risk of ergonomic problems such as musculoskeletal disorders and enhance employees’ performance.